Motivasi Mahasiswa Dalam Menyelesaikan Studi Di Jurusan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Padang - YULIANI, YULIANI; ernawati, ernawati; izwerni, izwerni (Journal of Home Economics and Tourism, 2013)
This study aim to determine the motivation in completing the studyÂ  in the Department of Family Welfare. The type of thisresearch is descriptive quantitative to explain and interpret the data.The samples in this study were all student dressmaking class from2005-207. Data was collected by distributing questionnaires. Theresult to analysis of data and level of achievement of the respondentsused the percentage rate technique. The result of study indicate thatstudent motivation in completing the study in the Department ofFamily Welfare at high enough category Keywords: motivation